+0  
 
0
76
2
avatar

Solve for x in terms of y and z, assuming \(y\neq 3\)\(xy = 3x + 2y + z.\)

 May 1, 2020
 #1
avatar+470 
+1

This is solving for x. :)

 

xy = 3x + 2y + z, right? So, we can divide both sides by y to get

 

x = (3x + 2y + z) / y :D

Is that it? Do we need to do anything more?

 May 1, 2020
 #2
avatar+111433 
+1

xy  =  3x  + 2y  + z

 

xy - 3x  =  2y  + z

 

x ( y - 3)  =  2y + z

 

           2y + z

x =    _______

            y -  3

 

 

 

 

cool cool cool

 May 1, 2020

12 Online Users

avatar